ROCK SLOPE STABILITY OF PONOROGO - PACITAN ROAD KM 232.5 USING ROCK MASS RATING (RMR) AND ROCPLANE SOFTWARE - Hasyim Alhadar; Arief Rachmansyah; Eko Andi Suryo (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2022)
Geological structures and discontinuities in the rock are weak areas and groundwater infiltration pathways. The existence of geological structures and discontinuities will reduce the level of rock shear strength and the main implication is to increase the chance of landslides. The purpose of this study was to determine the type of sliding on rock slopes, rock mass classification, and to determine the stability of the rock slopes. Kinematic analysis obtained landslide type, rock mass classification analysis including medium rock mass class with an RMR value of 53. Slope stability analysis based on the generalized criteria Hoek & Brown failure obtained a safety factor value of 1.55 with a slope angle of 60°. Slope stability analysis based on Mohr-Coulomb criteria obtained a safety factor value of 1.59 with a slope angle of 70°.